2021
DOI: 10.1155/2021/2520806
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model for Prediabetes Risk in Middle-Aged and Elderly Populations: A Prospective Cohort Study in China

Abstract: Background. To investigate indicators for prediabetes risk and construct a prediction model for prediabetes incidences in China. Methods. In this study, 551 adults aged 40–70 years had normal glucose tolerance (NGT) and normal hemoglobin A1c (HbA1c) levels at baseline. Baseline data including demographic information, anthropometric measurements, and metabolic profile measurements were collected. The associations between possible indicators and prediabetes were assessed by the Cox proportional-hazards model. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…Furthermore, both training and validation groups showed high predictive performance, indicating good generalizability. In addition, it must be noted that the incidence of prediabetes in our study population was lower than in other similar studies (10.7% vs. 20.0–26.3%) 30 , 31 . A closer analysis of the relevant indicators revealed higher levels of age and BMI in their study population, as well as a higher proportion of family history of diabetes, smoking, and alcohol consumption.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Furthermore, both training and validation groups showed high predictive performance, indicating good generalizability. In addition, it must be noted that the incidence of prediabetes in our study population was lower than in other similar studies (10.7% vs. 20.0–26.3%) 30 , 31 . A closer analysis of the relevant indicators revealed higher levels of age and BMI in their study population, as well as a higher proportion of family history of diabetes, smoking, and alcohol consumption.…”
Section: Discussioncontrasting
confidence: 74%
“…Categorizing them into groups will result in a loss of information and a reduced ability to detect real relationships 58 , 59 . In 2021, Jiahua Wu et al 31 developed a model to predict the risk of prediabetes in middle-aged and elderly populations in China based on WC, HbA1c, family history of diabetes, and FPG. The AUCs were 0.702.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with other studies, the FPG base was found to be the leading determinator for an increased FPG end . In 2021, We et al found that FPG was the most important predictor for prediabetes in a 3.35-year follow-up period among 551 Chinese subjects, aged from 40-70 years old [26]. However, that study used multiple logistic regression and provided a hazard ratio (HR: 2.284; 95% confidence interval: 1.556, 3.352; p < 0.001).…”
Section: Discussionmentioning
confidence: 98%
“…For example, hypertension [5], high total cholesterol [6], depression [7], glucocorticoids [8], chronic obstructive pulmonary disease (COPD) [9], osteoarthritis [10], and increased age have all been found to be associated with greater risk of developing T2D. Because risk factors of diabetes are well-known, many studies have applied machine learning (ML) models to clinical data to predict diabetes [11][12][13][14][15][16]. However, there are no Canadian studies developing prescriptive ML models to predict prediabetes.…”
Section: Introductionmentioning
confidence: 99%